Peripheral Mission and Christian Responsibility from the Margins: Christ Who Came to the Lowly - Hun, Kang Yong; Ndun, Yusak; Nehe, Restuman (Sekolah Tinggi Teologi Pelita Hati, 2025)
This paper examines the theological significance and practical implications of ‘Peripheral Mission’ through the lens of the World Council of Churches (WCC) statement Together Towards Life (TTL). By exploring the missional life of Jesus Christ and Dietrich Bonhoeffer’s ethics, this study examines the Christian responsibility for the Other in the context of mission. Reflecting on the reality of the situation of the marginalized during the COVID-19 pandemic particularly in Bali and other parts of Indonesia—this paper discusses how the church should participate in God’s mission (Missio Dei) not from the center but from the margins. It argues that the church must respond to God’s call by embracing ‘the poor and the excluded as agents, not merely as recipients. This approach embodies Christ who came to the lowly places, inviting the church to become a centrifugal community rooted in solidarity and transformative mission.